Mycorrhizal inoculation under water stress conditions and its influence on the benefit of host microbe symbiosis of Terminalia arjuna species - Atul Kumar Bhardwaj; K. K. Chandra; Rajesh Kumar (Bulletin of the National Research Centre, 2023)
Abstract Background Entisol is a very poor, compact, and low-water-holding capacity soil. They are obstacles to the plant's root system's penetration and the availability of water, particularly in dry months. However, Arbuscular mycorrhizae fungi (AMF) is used for seedling growth and reduces water stress in the plant. Results In this experiment, the growth parameters and the physiological activities of the plant were changed for the well watering (WW), fractionated watering (FW), and stopped/no watering conditions of the T. arjunaseedling. This experiment demonstrated higher mycorrhizal dependency (24.90%) under the FW condition than that of the WW condition (18.58%). Also the root colonization was higher (67%) under FW plants compared to WW plants (53%) associated with AMF+ in T. arjuna seedling. Photosynthesis was found 24.27% more with FW than the WW condition. Experiment' shows posivitivecorrelation between the photosynthesis and interval of no watering for AMF− plants (r2 = 0.873 for AMF− (control) and comparatively very weak for plants with AMF+ (r2 = 0.259 for AMF+ plants). Conclusions The findings confirms the use of AMF in entisol soil to improve plant growth and biomass by reducing edaphic stress.